Asenapine augmentation and treatment-resistant schizophrenia in the high-secure hospital setting. (October 2014) - Smith, E. Naomi; Durge, Vijay; Sengupta, Samrat; Das, Mrigendra
Introduction: Asenapine is a novel, recently introduced antipsychotic drug. It has a unique receptor profile and it is licensed in the UK for the treatment of bipolar-affective disorder. However, there is some evidence for its effectiveness in schizophrenia and it is licensed for schizophrenia treatment in a number of countries. Significant numbers of patients within the high-secure hospital setting suffer from treatment-resistant schizophrenia. Many patients fail to respond to adequate antipsychotic trials, and require trials of augmentation with other medications. Methods: We report on our experience of using asenapine for augmentation of other antipsychotic medications in two male patients with treatment-resistant schizophrenia and histories of interpersonal violence. The patients provided informed consent to participate in this case series. Data were collected from the patients' clinical records, incident reports and hospital medical centre records. These records were used to derive primary and secondary outcome measures. These included time spent in seclusion, verbal and physical aggression, numbers of incidents and metabolic parameters. Symptoms were rated pre- and postaugmentation using the Positive and Negative Syndrome Scale (PANSS) and Clinical Global Impression rating scales. Results: Both patients showed an improvement after the addition of asenapine. These improvements were characterized by a reduction in global PANSS scores, in the PANSS excitability component, a reduction in scores of violence, overall incidents and reduction in seclusion hours. Conclusions: We found asenapine to be an effective augmentation agent with other antipsychotics in both patients. Clinical improvement was noted within weeks. The case-series nature and small sample size limited our ability to draw firm conclusions from our data. However, retrospective analysis has allowed us to take a naturalistic approach that this augmentation strategy may be advantageous on an individual patient basis in a high-secure hospital setting.